Cartera vencida de la cooperativa de ahorro y crédito San José Ltda., agencia Guaranda, provincia Bolívar, año 2022. - Naula Quizhpilema, Paula Alexandra (2025)
This research aims to identify improvement strategies for the management of overdue loans in the "San José" Savings and Credit Cooperative Ltda., Guaranda branch, during the year 2022. The central problem lies in the increase of the delinquency rate caused by the non-compliance of loan payments by members, which directly affects the institution's liquidity and financial stability. The methodology applied was descriptive, bibliographic, and documentary, with a mixed approach (qualitative and quantitative). Techniques such as surveys and interviews were used, targeting credit management staff and delinquent members. The inductive and deductive methods were applied to analyze both the financial situation and the strategies implemented. The main findings show that, although the cooperative maintains a delinquency rate within the limits established by the Superintendency of Popular and Solidarity Economy (SEPS), there are weaknesses in the application of follow-up and recovery strategies, which limits a more effective management of overdue loans. As a result, a set of improvement strategies is proposed to strengthen the overdue loan recovery process, which will help optimize institutional profitability and improve member trust.